2019
DOI: 10.3390/cryst9010046
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Investigations of the Incomplete Spin Transition in a Single Crystal of [Fe(2-pytrz)2{Pt(CN)4}]·3H2O: Experiment and Theory

Abstract: Optical microscopy technique is used to investigate the thermal and the spatio-temporal properties of the spin-crossover single crystal [Fe(2-pytrz) 2 {Pt(CN) 4 }]·3H 2 O, which exhibits a first-order spin transition from a full high-spin (HS) state at high temperature to an intermediate, high-spin low-spin (HS-LS) state, below 153 K, where only one of the two crystallographic Fe(II) centers switches from the HS to HS-LS state. In comparison with crystals undergoing a complete spin transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…A good agreement is obtained between all these data, although the structural transition appears sharper with respect to the magnetic one. Similar conclusions are also found when comparing magnetic data with optical microscopy studies, performed on various SCO single crystals, which demonstrated that the transition temperature crucially depends on the crystal size and shape 17…”
Section: Resultssupporting
confidence: 81%
“…A good agreement is obtained between all these data, although the structural transition appears sharper with respect to the magnetic one. Similar conclusions are also found when comparing magnetic data with optical microscopy studies, performed on various SCO single crystals, which demonstrated that the transition temperature crucially depends on the crystal size and shape 17…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, switchable thin films [24,39,40] and nanoparticles [41][42][43] have also been synthesized and their properties analyzed. On the other hand, the spatiotemporal features at the macroscopic scale, accompanying the cooperative SCO materials exhibiting first-order transitions, remained quite unexplored until high-quality single crystals became available [44,45] and optical microscopy (OM) studies [46][47][48][49][50][51][52] were developed. As a result, the mechanism of the SCO transition on one single crystal was clarified, since it was identified that the transformation of a single crystal is governed by a nucleation and growth mechanism [51] in which the volume change at transition deploys long-range elastic interactions that delocalize the 2 of 15 strain field at long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable images of spin state domain nucleation, growth, and propagation of domain boundaries upon a HS/LS transition have been obtained using optical microscopy measurements down to a typical micrometer resolution. [15][16][17][18][19] The quantitative analysis of the propagation of the domain boundary allowed estimating the corresponding velocity, which is several orders of magnitude slower than the sound velocity in molecular crystals. 20 Micro-raman spectroscopy and atomic force microscopy have provided additional spin state mapping in single crystals.…”
Section: Incommensurate Hs/ls Pattern Developmentmentioning
confidence: 99%
“…Strong elastic interactions result in abrupt first order spin transitions, associated with thermal hysteresis, and remarkable instabilities in the light-induced spin transition regime. Optical microscopy measurements performed in various thermal and optical excitation conditions [15][16][17][18][19][19][20][21] have clearly shown the major importance played by the development of structural and spin state domains upon all these processes. Altogether, the SCO process occurs on several spatial scales from the microscopic molecular level to the mesoscopic scale.…”
Section: Introductionmentioning
confidence: 99%